2005
DOI: 10.1021/cm050612o
|View full text |Cite
|
Sign up to set email alerts
|

Mesomorphic Hexabenzocoronenes Bearing Perfluorinated Chains

Abstract: IntroductionExtended polyaromatic hydrocarbons (PAH) are finding increasing interest among other self-assembled supramolecular systems due to their pronounced tendency for formation of extended π-stacked assemblies. These have many potential properties, such as a high electron density which allows their use in promising applications in molecular electronics. 1 However, the main drawback of these rigid polycondensed molecules resides in the difficulty of their synthesis and their very low solubility which preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 45 publications
(96 reference statements)
2
50
0
3
Order By: Relevance
“…Phases of this kind (discotic lamellar) have been documented for other discotic systems. [48] The XRD pattern recorded for 1 b at 80 8C (Figure 1) is indicative of the formation of a lamello-columnar mesophase (L Col ), similar to those observed recently for lath-like perylene diimides [49] and for disc-lath mixtures of phthalocyanines and perylenes. [50] Three sharp reflections, with reciprocal spacings in the ratio 1:2:3, are observed in the small-angle region at 34.8, 17.5, and 11.55 , respectively.…”
supporting
confidence: 82%
“…Phases of this kind (discotic lamellar) have been documented for other discotic systems. [48] The XRD pattern recorded for 1 b at 80 8C (Figure 1) is indicative of the formation of a lamello-columnar mesophase (L Col ), similar to those observed recently for lath-like perylene diimides [49] and for disc-lath mixtures of phthalocyanines and perylenes. [50] Three sharp reflections, with reciprocal spacings in the ratio 1:2:3, are observed in the small-angle region at 34.8, 17.5, and 11.55 , respectively.…”
supporting
confidence: 82%
“…[157] [159] Watson, Müllen und Bard synthetisierten ein Hexaphytyl-HBC 63 f (Schema 27), das zwischen À36 und 231 8C in einer hexagonal geordneten Mesophase vorlag. [160] Auf der Grundlage von Photoleitfähigkeitsmessungen wurden zwei Orientierungen vorgeschlagen, nämlich eine Anordnung der [163] und Tsukruk [164] [11] Abbildung 31.…”
Section: Hexa-peri-hexabenzocoronen-derivateunclassified
“…On the other hand, several reports were also published on columnar liquid crystals possessing fluoroalkyl side chains [29][30][31][32][33][34][35][36][37][38][39][40]. For example, it was reported that all tapered building blocks, and the self-assembly polymers (perfluorinated methylenic groups of their alkyl tails) into tubular supermolecular architectures show an enantiotropic hexagonal columnar mesophase.…”
Section: Introductionmentioning
confidence: 99%